National language in science: The case of Latvian - Dubova, Agnese; Laiveniece, Diāna; Proveja, Egita; Egle, Baiba (Journal of Education Culture and Society, 2020)
Aim. To show and describe the current situation in Latvian language as a case study of the problem about the place of a national language and its existence in sciences in modern globalised times, when the dominance of English as the lingua franca of science grows. Methods. A descriptive method, including literature review of language of science used globally. Empirical discourse content analysis was conducted; it examined various documents, including Latvian legal texts that governs the rights and rules of Latvian language use, as well as a wide array of mainly online media. Results. During the study, 21 different sources and 304 online comments under articles relating to the issue were analysed. The material revealed that there is a breadth of opinions, ranging from the Ministry stance to organisations and the general public. It could be said that the main trend in the opinions can be described as follows: there is a variety of language options – a dissertation written only in Latvian; a dissertation written in English; a choice of language that is up to the doctoral student. This would ensure that the language choice fits the doctoral students’ goals and field of research and making English mandatory would not likely lead to guaranteed scientific excellence as what matters is the research itself, not the language. Conclusions. National language of science is a current issue in Latvia, as there is a need for state language use in the scientific register. The discussed Ministry document is still a draft report and it is not yet known what final decisions on the PhD process and dissertation language will be taken. Latvian is a scientific language and it should be recognised as one of the languages used in science within the international scientific discourse.